BENTHIC CLASSIFICATION OF CORALREEFS USING SVM CLASSFIER - SURESH KUMAR NAGARAJAN; SENTHIL MURUGAN BALAKRISHNAN (International Journal of Pharma and Bio Sciences, 2015)
The objective of the proposed work is to develop a SVM based classification system that identifies the state and type of the coral reef images using Support Vector Machine (SVM) classifier. Many conservation programs and monitoring surveys are conducted around the world to preserve coral reefs which play an important role in marine biodiversity and human livelihood. A basic way of monitoring reefs is to determine the population of different “benthos” or organisms in a reef area such as living or dead corals, algae, etc.. It is utilized by marine scientists to deduce if a reef ecosystem is healthy, dying or at risk. The proposed work describes the classification procedure for processing coral reef images and rendering the required data through proper visualization tools.